Alpinumisoflavone and abyssinone V 4′-methylether derived from Erythrina lysistemon (Fabaceae) promote HDL-cholesterol synthesis and prevent cholesterol gallstone formation in ovariectomized rats. (14th February 2015) - Mvondo, Marie A; Njamen, Dieudonné; Kretzschmar, Georg; Imma Bader, Manuela; Tanee Fomum, Stephen; Wandji, Jean; Vollmer, Günter
Abstract: Objectives: E rythrina lysistemon was found to improve lipid profile in ovariectomized rats. Alpinumisoflavone (AIF) and abyssinone V 4′-methylether (AME) derived from this plant induced analogous effects on lipid profile and decreased atherogenic risks. To highlight the molecular mechanism of action of these natural products, we evaluated their effects on the expression of some estrogen-sensitive genes associated with cholesterol synthesis ( Esr1 and Apoa1 ) and cholesterol clearance ( Ldlr, Scarb1 and Cyp7a1 ). Methods: Ovariectomized rats were subcutaneously treated for three consecutive days with either compound at the daily dose of 0.1, 1 and 10 mg/kg body weight (BW). Animals were sacrificed thereafter and their liver was collected. The mRNA of genes of interest was analysed by quantitative real-time polymerase chain reaction. Key findings: Both compounds downregulated the mRNA expression of Esr1, a gene associated with cholesterogenesis and cholesterol gallstone formation. AME leaned the Apoa1/Scarb1 balance in favour of Apoa1, an effect promoting high-density lipoprotein (HDL)-cholesterol formation. It also upregulated the mRNA expression of Ldlr at 1 mg/kg/BW per day (25%) and 10 mg/kg/BW per day (133.17%), an effect favouring the clearance of low-density lipoprotein (LDL)-cholesterol. Both compounds may also promote the conversion of cholesterol into bile acids as they upregulated Cyp7a1  mRNA expression. Conclusion: AIF and AME atheroprotective effects may result from their ability to upregulate mechanisms promoting HDL-cholesterol and bile acid formation.